A series of lanthanide–quinoxaline-2, 3(1H, 4H)-dione complexes containing 1D chiral Ln2O3 (Ln = Eu, Tb, Sm, Dy) chains: luminescent properties and response to small molecules. Issue 53 (29th October 2021) - Hassan, Sadaf ul; Farid, Muhammad Asim; Wang, Yingxia
Abstract : A series of isostructural lanthanidequinoxaline-2, 3(1 H, 4 H )-dione containing 1D chiral chains shows high sensing effect toward the small solvent molecules, in which tertiary butanol was an excellent sensitizer, while tetrahydrofuran was a highly quenching species. Abstract : Five new isostructural lanthanide–organic complexes, [Ln2 O2 (OH)(HQXD)(H2 QXD)2 ]·H2 O (Ln = Eu 1, Tb 2, Sm 3 Dy 4 and Gd 5 ; H2 QXD = quinoxaline-2, 3(1 H, 4 H )-dione), have been synthesized under hydrothermal conditions. These complexes are characterized by powder X-ray diffraction (PXRD), infrared spectroscopy (IR), elemental analysis (EA), thermogravimetric-differential thermal analysis (TG-DTA) and photo-luminescent spectroscopy. Single crystal X-ray diffraction analysis of complex 1 revealed that the structure featured in 1D chiral "Eu2 O3 " chains surrounded by coordinating organic ligands. These chains are interconnected via hydrogen bonding and offset π⋯π stacking interactions of the ligands to form the 3D supramolecular frameworks. The photo-luminescence studies for complexes 1–5 disclosed that the ligand (H2 QXD) showed an antenna effect to transfer energy toward the lanthanide cations. The energy transfer mechanism investigations show that the energy transition from the triplet energy level ( 3 ππ*) of ligand H2 QXD to the Tb 3+ cation is more effective than to the Eu 3+, Sm 3+ and Dy 3+ ions; therefore it has been selected as a representative to examine the potential for sensing small molecules. Complex 2′, which was obtained by the heating treatment of 2 at 150 °C, displayed a high luminescence sensitivity towards small solvent molecules. Tertiary butanol ( t -butanol) was found to be an excellent sensitizer, while tetrahydrofuran (THF) was a highly quenching species. Complex 2′ could regain a higher photo-luminescence intensity after treating for 5 cycles with t -butanol, revealing a prospect for reusability.